ANALISIS SELF CONFIDENCE DALAM MENINGKATKAN MOTIVASI BERWIRAUSAHA MAHASISWA MBKM KEWIRAUSAHAAN PROGRAM STUDI PENDIDIKAN EKONOMI - Safika, Nurul Ain; Asriati, Nuraini; Budiman, Jumardi (Universitas Tanjungpura, 2024)
This study aims to analyze self- confidence in improving entrepreneurship motivation MBKM students entrepreneurship Economic Education FKIP Tanjungpura University. This research approach uses qualitative approach with descriptive study research. Informans in this study are students of Economic EDUCATION fkip Tanjungpura University of class of 2021 and 2022 as many as 13 people. The informant category is students who have followed MBKM Entrepreneurship. Data collection techniques use direct interviews and observation. The result of this study shows that students self confidence can increase after participating in MBKM entrepreneurship activities and can provide ideas, implement to make finished products that have been approved by the market and aspects that can be increase entrepreneurial motivation is aspect 1) confidence in the ability of self by improving skills; 2) optimistic by always thinking positively; 3) objective by continuing to learn from the surrounding to learn from the surrounding environment; 4) responsible by not harming the surrounding environment; 5) realistic and rational can balance the shortcomings of self and facts in the field. Motives that increase entrepreneurial motivation are 1) need for achievement, namely achievement in the from of income: 2) need for power, namely to make changes and guide the team in achieving maximum potential; 3) need for affiliation, namely building good relationship so that they can work together